Leverage constraints and bank monitoring: Bank regulation versus monetary policy - Florian Böser; Hans Gersbach (ETH Zurich, CER-ETH - Center of Economic Research, 2021)
Bank leverage constraints can emerge from regulatory capital requirements as well as from central bank collateral requirements in reserve lending facilities. While these two channels are usually examined separately, we are able to compare them with the help of a bank money creation model in which central bank reserves have to be acquired to settle interbank liabilities. In particular, we show that with regard to bank monitoring, monetary policy via collateral requirements leads to a unique collateral leverage channel, which cannot be replicated by standard capital requirements. Through this channel, banks can expand loan supply and deposit issuance when they face liquidity constraints, by raising the collateral value of their loans with tighter monitoring of firms. The collateral leverage channel can improve welfare beyond standard bank capital regulation. Our results may inform current policy debates, such as the design of central bank collateral frameworks or the question whether monetary policy remains effective in times with large central bank reserves.
Keywords: E42; E52; E58; G21; 330; leverage; banks; monitoring; bank regulation; monetary policy